The Part of Information Certainty in the Rating Process of Firms and Individuals - Kirilov, Rosen (Research Papers, 2009)
During assessment process of credit rating an entity uses and applies different procedures. Each one of these procedures is based on its own information certainty and is used for particular client’s data. The public credit rating is a current analysis of a future solvency of the entity which is a client of the external credit assessment institution (ECAI). This analysis is based on client’s information and/ or other information from eligible sources. The analysis eligibility could be guaranteed only if client’s information is correct, comprehensive, unadulterated and current. The analysis aim is not to be taken as a recommendation for a bank credit or for security investments, neither to be taken as a credit warranty. ECAI are not allowed to accomplish an investment consultation for corporative clients, neither to be a negotiator between a client and potential investors.